Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1029/2019wr026129
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Small‐Scale Forest Snow Patterns Using an Energy Balance Snow Model With a One‐Layer Canopy

Abstract: Modeling spatiotemporal dynamics of snow in forests is challenging, as involved processes are strongly dependent on small-scale canopy properties. In this study, we explore how local canopy structure information can be integrated in a medium-complexity energy balance snow model to replicate observed snow patterns at very high spatial resolutions. Snow depth distributions simulated with the Flexible Snow Model (FSM2) were tested against extensive experimental data acquired in discontinuous subalpine forest stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 95 publications
(191 reference statements)
6
62
0
Order By: Relevance
“…This study furthers the work of Mazzotti et al (2020) by addressing two major research needs identified in their conclusion. First, we attempt to overcome the limitations of existing model evaluation efforts by validating our hyper‐resolution FSM2 simulations of the forest snowpack evolution with novel data sets acquired with mobile multisensor platforms.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…This study furthers the work of Mazzotti et al (2020) by addressing two major research needs identified in their conclusion. First, we attempt to overcome the limitations of existing model evaluation efforts by validating our hyper‐resolution FSM2 simulations of the forest snowpack evolution with novel data sets acquired with mobile multisensor platforms.…”
Section: Introductionsupporting
confidence: 79%
“…Model features specific to the enhanced FSM2 as introduced in this study are detailed below. Note that we only outline new options added to the original FSM2 version presented in Mazzotti et al (2020). For a comprehensive description of the original FSM2 canopy module, we refer to the Appendix in their publication.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 3 more Smart Citations